The early Amazons : modern and ancient perspectives on a persistent myth - Blok, Josine. (Religions in the Graeco-Roman World, 1995)
The Early Amazons offers a new understanding of the ancient Amazon myth, situating mythical representations in the realm of cultural history. The first section examines how the Amazons have presented a challenge to views on history, myth and gender in classical mythology from the late eighteenth century up to the impact of structuralism. Topics included are nineteenth-century historiography and the interest in linguistics. The second section sheds new light on the culture of archaic Greece, offering a coherent assessment of literary and visual representations. Taking mythical narrative as a form of oral storytelling, it shows the emergence of the Amazon motif and its meaning in the world of epic. Iconographical analysis reveals how the visual arts have made a contribution of their own to the imaginary presence of the Amazons.